Reflection iii: Transnationalisation, Television Formats and the Universal. Issue 2 (July 2013) - Knox, Simone
This reflection argues that, despite various good reasons for approaching the notion of the 'universal' with caution, cultural theorists should give up their resistance to the universal. The prominence of formats in today's television suggests that the time is ripe to do. Intentionally or not, accounts of difference implicitly also often reveal sameness; the more we probe heterogeneity, the more likely we are to encounter something that remains consistent and similar. Thus, it is time to collaborate with scholars from the numerous disciplines for which the universal has long had validity and pertinence.